Injury-related fear in athletes returning to sports after anterior cruciate ligament reconstruction - A quantitative content analysis of an open-ended questionnaire - Shunsuke Ohji; Junya Aizawa; Kenji Hirohata; Takehiro Ohmi; Sho Mitomo; Hideyuki Koga; Kazuyoshi Yagishita (Elsevier, 2021)
Background/objective: Injury-related fear during sport activities are major psychological factors inhibiting a person's return to sports (RTS) following anterior cruciate ligament reconstruction (ACLR). Currently, there are no studies that quantitatively analyse the open-ended questionnaire for knee injury-related fear in post-ACLR athletes.The purpose of this study was to identify knee injury-related fear in athletes who return to ball-centric sports via the use of an open-ended questionnaire. We aimed to determine the main concepts of injury-related fear according to sex, type of sport, and participation level. Methods: In this study, a quantitative analysis of an open-ended questionnaire was used to examine the type of fear athletes experience after returning to ball-centric sports. The RTS and fear questionnaire collected open-ended questionnaire to knee injury-related fear during sport activities; this questionnaire was completed at the outpatient visit post-RTS. Quantitative content analysis was performed to extract frequently occurring words from the responses to the questionnaire to create a co-occurrence network. The resulting co-occurrence network and extracted words were used to create concepts regarding knee injury-related fear. The relationship between each concept and subject demographics (sex, returned sports events, and participation level) were analysed using the chi-squared test. Results: Fifty-four athletes (30 females and 24 males) aged 16-45 [median age: 21.2; interquartile range (IQR): 11.0] years with an average RTS of 8.0 (IQR: 3.3) months from ACLR participated in the study. A total of 79 responses were included in the analysis. The knee injury-related fear can be summarized as follows: (1) Quick response to the opponent; (2) Ball-related play; (3) Jump-landing; (4) Contact; (5) Loss of balance; and (6) Athletic movement. Chi-squared tests showed that athletes participating in sport events with potential contact with an opponent (soccer, futsal, basketball, handball, lacrosse, and ultimate (frisbee)) were more likely to experience fear in quick response to the opponent (P < 0.01, adjusted residual = 2.943, ϕ = 0.301). Conclusion: The knee injury-related fear can be summarized into six concepts. Post-ACLR athletes participating in ball-centric sports need to assess fear in situations such as quick responses to the opponent's movements and ball-related play, in addition to simple movements such as jumping, cutting, and contact.